Good governance practice for the shariah compliant hotel in Malaysia: an insightful study - Ruzulan, Zulaipa; Hassan, Rusni; Jamaludin, Mohammad Aizat; Saidin, Nurulaina (Human Resource Management Academic Research Society, 2023)
The performance of the Shariah compliant hotel has a strong relationship with the governance approach adopted by the hotel. On this occasion, poor governance practice may result in the mismanagement of the Shariah compliant hotel’s operation where the Shariah compliant hotel does not comply with the Shariah requirements. Since a limited study focuses on the good governance practice for the shariah compliant hotel, this paper will investigate the essential elements of good governance for the Shariah compliant hotel. This study adopts a qualitative research methodology where the document analysis technique was used to collect the data and then analyzed using content analysis. The finding has shown that the governance practice of the Shariah compliant hotel is still at a minimum level where the Shariah compliant hotel focuses more on the halal certification requirement awarded to them. Thus, there is a need for the regulator to establish a proper policy on the best governance practice for the Shariah compliant hotel.